Community‐acquired methicillin‐resistant Staphylococcus aureus nasal abscesses in a lower socioeconomic urban population. Issue 8 (12th February 2013) - Wang, Andrea S.; Roure, Rita M.; Pearlman, Aaron N.
<x xml:space="preserve">Abstract</x> Background To determine the prevalence of community‐acquired methicillin‐resistant S. aureus (CA‐MRSA) and methicillin‐sensitive S. aureus (MSSA) nasal abscesses in a lower socioeconomic status urban population over a 5‐year period. Methods A retrospective chart review of 29 consecutive patients with nasal abscess cultures performed in the otolaryngology clinic from 2007 to 2012. Results Twenty‐nine cases of nasal abscesses were identified. All cultures grew S. aureus; 34.5% were MSSA and 65.5% were CA‐MRSA. Comparing CA‐MRSA and MSSA, there was no statistically significant increase in prevalence of CA‐MRSA over 5 years; and there was no statistical difference comparing gender, year, or age. There was a high rate of erythromycin resistance (15/19) and a low rate of sulfamethoxazole/trimethoprim (2/19) and clindamycin (1/19) resistance in the CA‐MRSA cases. Conclusion In this population, the proportion of CA‐MRSA nasal abscesses is nearly twice that of MSSA nasal abscesses. The overall prevalence of CA‐MRSA appears to be stable over the past 5 years. This may represent a stabilization of CA‐MRSA colonization in this community. An awareness of the high proportion of CA‐MRSA will allow for the appropriate selection of antibiotic therapy.